2003
DOI: 10.1016/s0014-5793(03)00934-7
|View full text |Cite
|
Sign up to set email alerts
|

From the first to the second domain of gelsolin: a common path on the surface of actin?1

Abstract: We present the 2.6 A î resolution crystal structure of a complex formed between G-actin and gelsolin fragment Met25Ĝ ln160 (G1+). The structure di¡ers from those of other gelsolin domain 1 (G1) complexes in that an additional six amino acid residues from the crucial linker region into gelsolin domain 2 (G2) are visible and are attached securely to the surface of actin. The linker segment extends away from G1 up the face of actin in a direction that infers G2 will bind along the same long-pitch helical strand a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
45
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…This study showed that the two stretches of amino acid sequences, the residues 148 -152 (GFKHV) in the g1-g2 linker and the residues 108 -114 (LDDYLNG) in the G1 domain, as well as the exact length of the g1-g2 linker are critical for the F-actin depolymerization function of the gelsolin (16,17). The structure of the F-actin depolymerization-competent 25-160-residue fragment of gelsolin in complex with the actin supported the hypothesis that the partial G2 domain binds along the side of the actin filament in such a way that it targets the G1 domain to intercalate between the actin subunit bound to G2 and the adjacent actin subunit and to rupture the noncovalent interactions holding them together (18). The opening of the G1 domain from rest of the molecule might thus be a prerequisite for the F-actin depolymerization function of gelsolin as has also been supported by the recent studies (3,4).…”
mentioning
confidence: 85%
“…This study showed that the two stretches of amino acid sequences, the residues 148 -152 (GFKHV) in the g1-g2 linker and the residues 108 -114 (LDDYLNG) in the G1 domain, as well as the exact length of the g1-g2 linker are critical for the F-actin depolymerization function of the gelsolin (16,17). The structure of the F-actin depolymerization-competent 25-160-residue fragment of gelsolin in complex with the actin supported the hypothesis that the partial G2 domain binds along the side of the actin filament in such a way that it targets the G1 domain to intercalate between the actin subunit bound to G2 and the adjacent actin subunit and to rupture the noncovalent interactions holding them together (18). The opening of the G1 domain from rest of the molecule might thus be a prerequisite for the F-actin depolymerization function of gelsolin as has also been supported by the recent studies (3,4).…”
mentioning
confidence: 85%
“…The goal of this study was to better describe the structural basis of the interaction of villin with Ca 2ϩ to elucidate the molecular basis of cytoskeletal reorganization by villin. Of all the proteins of the villin superfamily, the Ca 2ϩ -binding sites are best described for the homologous protein gelsolin, which has been crystallized in the presence of actin and Ca 2ϩ ions (15)(16)(17)(18)(19). However, even for this protein, the Ca 2ϩ binding sites regulating actin capping and actin severing have not been functionally distinguished.…”
mentioning
confidence: 99%
“…From sequence similarity, they inferred common ancestry. The enlarged WH2 domain is gaining currency [2][3][4], yet evidence for such a relationship is lacking.b-Thymosins are 43 residue peptides with a role in actin dynamics as monomer-sequestering agents [5]. Recently, a number of proteins containing internal tandem repeats of sequences very similar to monomeric b-thymosins have been identified, first in Drosophila and Caenorhabditis [6], more recently in Ciona, Dermacentor and Hermissenda [7].…”
mentioning
confidence: 99%
“…From sequence similarity, they inferred common ancestry. The enlarged WH2 domain is gaining currency [2][3][4], yet evidence for such a relationship is lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation